2018
DOI: 10.1111/1460-6984.12403
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐directed commentaries during children's hearing habilitation appointments: a practice in family‐centred care

Abstract: The parent-directed commentaries identified in this study provide an example of the practical, interactional resources that health professionals can draw on within paediatric appointments to facilitate FCC with parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…It was noted that 99 parents felt that their interaction with the therapist was good. Similarly, Ekberg and Hickson [ 12 ] reported that therapist was able to engage the parents in the interaction with the child in the therapy session. Thus, there were no communication difficulties between parents and hearing habilitation providers.…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that 99 parents felt that their interaction with the therapist was good. Similarly, Ekberg and Hickson [ 12 ] reported that therapist was able to engage the parents in the interaction with the child in the therapy session. Thus, there were no communication difficulties between parents and hearing habilitation providers.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection procedure for this study is described in detail elsewhere [20]. All participants provided written informed consent.…”
Section: Procedures and Analysismentioning
confidence: 99%
“…The video data was transcribed using the Jeffersonian and Mondada transcription systems [26,27]. The data was analysed using conversation analysis (CA), a well-established method for examining healthcare interactions [28][29][30], including in audiology and speech pathology [20,[31][32][33]. For the current study, the data was searched for all questions from parents (including repeated or re-formulated questions).…”
Section: Procedures and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A holistic approach to care in the hearing loss setting improves the overall health outcomes of the child, fostering strong interpersonal relationships between the child and parent [ 13 ]. Additionally, higher staff satisfaction and more effective use of healthcare resources have also been associated with family-centred care [ 12 , 14 ]. Supporting parents’ needs is an important component of achieving the best possible outcomes of a child diagnosed with hearing loss.…”
Section: Introductionmentioning
confidence: 99%